Modern Approaches to the Diagnosis and Treatment of Lower Urinary Tract Disorders - Buczkowski, Jakub; Biaduń, Weronika; Dobosz, Mateusz; Romanowska, Aleksandra; Padkowska, Aleksandra; Rogowska, Kinga; Borawski, Michał; Ciuła, Aleksandra; Arciszewska, Klaudia; Pieniążek, Jakub Maciej (Journal of Education, Health and Sport, 2025)
Lower urinary tract disorders, including conditions such as overactive bladder (OAB), stress urinary incontinence (SUI), neurogenic voiding dysfunction, and nocturia, represent a significant health concern that greatly affects patients’ quality of life worldwide. These disorders not only diminish life comfort but can also lead to physical and psychological complications, including chronic pain, urinary tract infections, sleep disturbances, depression, and social isolation. It is estimated that these conditions affect both adults and children, with prevalence rates ranging from 1% to 20% in pediatric populations and up to 67% among older adults. Modern medicine offers a variety of treatment options for lower urinary tract disorders, including pharmacotherapy, behavioral therapies, surgical interventions, and advanced technological approaches such as neuromodulation. Advances in the understanding of the pathophysiology of these conditions, along with the development of medical technologies, have significantly improved diagnostic and therapeutic capabilities. Nonetheless, managing patients with lower urinary tract disorders remains a clinical challenge, particularly for those with treatment-resistant symptoms who do not respond to conventional therapies.